FUNCTIONAL AND ANATOMICAL DIFFERENCES BETWEEN CONTINENT AND INCONTINENT MEN POST RADICAL PROSTATECTOMY ON URODYNAMICS AND 3T MRI: A PILOT STUDY - Cameron, Anne P. (2014)
AIMS: There are competing hypotheses about the etiology of post prostatectomy incontinence (PPI).The purpose of this study was to determine the anatomical and functional differences between men with and without PPI. METHODS: Case control study of continent and incontinent men after radical prostatectomy who underwent functional and anatomic studies with urodynamics and 3.0 Tesla MRI. All men were at least 12 months post prostatectomy and none had a history of pelvic radiation or any prior surgery for incontinence. RESULTS: Baseline demographics, surgical approach and pathology were similar between incontinent (cases) (n=14) and continent (controls) (n=12) men. Among the cases, the average 24 hour pad weight was 400.0 ±176.9 grams with a mean of 2.4 ±0.7 pads per day. Urethral pressure profiles at rest did not significantly differ between groups; however with a Kegel maneuver the rise in urethral pressure was 2.6 fold higher in controls. On MRI, the urethral length was 31–35% shorter and the bladder neck was 28.9 degrees more funneled in cases. There were no differences in levator ani muscle size between groups. There was distortion of the sphincter area in 85.7% of cases and in 16.7% of controls (p=0.001). CONCLUSIONS: Men with PPI were not able to increase urethral pressure with a Kegel maneuver despite similar resting urethral pressure profiles. Additionally, incontinent men had shorter urethras and were more likely to have distortion of the sphincter area. All suggesting that the sphincter in men with PPI is both diminutive and poorly functional.